2010
DOI: 10.4049/jimmunol.0903489
|View full text |Cite
|
Sign up to set email alerts
|

Expanded CD23+/CD21hi B Cells in Inflamed Lymph Nodes Are Associated with the Onset of Inflammatory-Erosive Arthritis in TNF-Transgenic Mice and Are Targets of Anti-CD20 Therapy

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(161 citation statements)
references
References 41 publications
(60 reference statements)
16
134
1
Order By: Relevance
“…These results of the lymph node analyses differ from those in a previous study on peripheral blood, in which gene expression profiling of at risk individuals revealed a low B-cell signature especially in those individuals who developed arthritis after follow-up 20. It is tempting to speculate that the B cells are retained in the lymph nodes, to ensure maturation and differentiation during the immune response which would be in line with findings in animal models of arthritis 12 13…”
Section: Discussioncontrasting
confidence: 44%
“…These results of the lymph node analyses differ from those in a previous study on peripheral blood, in which gene expression profiling of at risk individuals revealed a low B-cell signature especially in those individuals who developed arthritis after follow-up 20. It is tempting to speculate that the B cells are retained in the lymph nodes, to ensure maturation and differentiation during the immune response which would be in line with findings in animal models of arthritis 12 13…”
Section: Discussioncontrasting
confidence: 44%
“…Even though this model differs from human RA due to the initiating role of TNF-α and the absence of detectable rheumatoid factor, it does incorporate a number of features relevant to human rheumatoid arthritis [74]. Despite the lack of rheumatoid factor, hTNF-tg mice develop disease-associated B cell changes, and B cell depletion is protective [75]. Further, hTNF-tg mice develop a complex proinflammatory cytokine response with upregulation of interleukin-1 (IL-1) and interleukin-6 (IL-6) that occurs in conjunction with the development of early lesions [16].…”
Section: Tnf-α Driven Modelsmentioning
confidence: 99%
“…The following antibodies were used for staining of the lung sections: ␣SMA (1:100) (Sigma-Aldrich, St. Louis, MO) 19,20 ; phosphoP38 (1:50), phosphoJNK (1:100), and phosphoERK (1:100) (Cell Signaling Technology, Danvers, MA) 21,22 ; Ki-67 (1:100) (Epitomics, Burlingame, CA) 23,24 ; and VEGF (1:100) (Novus Biologicals, Littleton, CO). 25 Immunohistochemical staining was performed according to our previously described method.…”
Section: Immunohistochemistrymentioning
confidence: 99%